2020
DOI: 10.1038/s41416-020-0811-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and clinical impact of PD-L2 and PD-L1 expression in a cohort of 437 oesophageal cancers

Abstract: Background The PD-1/PD-L1 pathway plays critical roles in tumour immunology, and serves as an immune-based therapeutic target. Less is known regarding PD-L2, another ligand of PD-1, and its relation to clinical outcome in human cancers. Methods We used a database of 437 surgically and 100 endoscopically resected oesophageal cancers (squamous cell carcinoma, n = 483; adenocarcinoma, n = 36; others, n = 18) to evaluate PD-L2 and PD-L1 expression by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…In head and neck squamous cell carcinoma, PD‐L2 status has been reported to be a significant predictor of progression‐free survival with pembrolizumab independently of PD‐L1 36 . We have recently reported that the expression of PD‐L2 as well as PD‐L1 is associated with unfavorable clinical outcomes in esophageal cancer 37 . We have also found that PD‐L2 and PD‐L1 exhibit distinct expression patterns during tumor development and variations in responses to chemotherapeutic agents.…”
Section: Programmed Death‐ligand 2 Expression On Cancer Cellsmentioning
confidence: 83%
“…In head and neck squamous cell carcinoma, PD‐L2 status has been reported to be a significant predictor of progression‐free survival with pembrolizumab independently of PD‐L1 36 . We have recently reported that the expression of PD‐L2 as well as PD‐L1 is associated with unfavorable clinical outcomes in esophageal cancer 37 . We have also found that PD‐L2 and PD‐L1 exhibit distinct expression patterns during tumor development and variations in responses to chemotherapeutic agents.…”
Section: Programmed Death‐ligand 2 Expression On Cancer Cellsmentioning
confidence: 83%
“…Though this is was mainly in squamous cell carcinoma, the authors found no significant correlation between PD-L2 and PD-L1 expression. However, these data may indicate evaluation of both PD-L2 and PD-L1 expression may be clinically important [31].…”
Section: Discussionmentioning
confidence: 98%
“…Due to low response rates among EC patients, however, further efforts are needed to elucidate the resistance mechanism of immunotherapy. Among all the patients with EC, less than 20% of them express PD-L1 ( Okadome et al, 2020 ), which means a certain number of patients with EC are hard to get any therapeutic benefit from immune checkpoint inhibitors. Moreover, the expression of PD-L1 on the cell surface was found to be highly heterogeneous in EC ( Yan et al, 2019 ).…”
Section: Cellular Componentsmentioning
confidence: 99%
“…Notably, the combination of PD-L1 expression and TILs status has the potential to serve as predictive biomarkers for patients with EC ( Yagi et al, 2019a ). PD-L2 has also been demonstrated to be associated with a worse prognosis in EC ( Ohigashi et al, 2005 ; Okadome et al, 2020 ). The identification of these biomarkers contributes not only to prognosis prediction but also to patient classification and selection ( Baba et al, 2020 ).…”
Section: Cellular Componentsmentioning
confidence: 99%